Surgical treatment of cryptorchidism: current insights and future directions - Pakkasjärvi, Niklas; Taskinen, Seppo (Frontiers in Endocrinology, 2024)
Cryptorchidism presents with an incidence of 1-5% with potential long-term implications on future fertility and overall health. This review focuses on surgical treatment modalities, their impact on testicular development, and function while addressing the Nordic consensus statement as well as current European Association of Urology (EAU) and American Urological Association (AUA) guidelines. Congenital and acquired cryptorchidism present distinctive challenges in surgical management, with different implications for fertility. While congenital cryptorchidism entails a risk to fertility and warrants early intervention, both retractile testes and acquired cryptorchidism also pose risks to fertility potential, underscoring the importance of evaluating treatment options. Testicular location and the child's age form the basis of a practical classification system for undescended testicles. Early diagnosis by clinical examination enables timely treatment. Imaging is reserved for selected cases only. Following guidelines, orchidopexy is recommended between 6-12 months of age for congenital cryptorchidism. Evidence increasingly suggests the benefits of early surgery for promoting testicular health and fertility potential. Current surgical options range from open to laparoscopic techniques, with the choice largely determined by the location and accessibility of the undescended testicle. The advancement in laparoscopic approaches for non-palpable testes underscores the evolving landscape of surgical treatment. Sequential surgeries may be required depending on the mobility of the undescended testes. More research is needed to explore both the potential and limitations of hormonal therapy, which is secondary to surgical treatment and can selectively have a role as adjunct to surgery. Long-term follow-up is imperative to evaluate fertility outcomes, risk of testicular malignancy, and psychological impact. By integrating current guidelines with the latest evidence, this review intends to facilitate a comprehensive understanding of cryptorchidism, thereby optimizing patient management and outcomes.